Avaliação do Programa Bolsa Família a partir das trajetórias de mulheres do Pirambu, em Fortaleza-CE: percepções sobre cidadania em processo - Conceição, Samara Hipólito da (2014)
The research presents a study of the life histories of four women benefited from the BolsaFamília Program in Pirambu neighborhood in Fortaleza-CE, conducted in 2013, mainly evaluating possible perceptions of citizenship present in this process. Search specific objectives: to identify and understand the changes in the lives of the families surveyed, from the inclusion in the Program, focusing on the following aspects: social, work, food, meeting the conditionalities required, surveyed household access to other social policies. Narrative, we evaluate the meanings attributed by these women about the concept of citizenship , from the notion of social rights identified. The assessment of life trajectories traveled by individuals surveyed considers various times: the inscription on CadÚnico the early receipt of the benefit and the present moment. The research refers primarily to social policy category, contextualizing its emergence on the international and national level, which is the scenario where emerge the first experiences of Income Transfer Programs in Brazil and abroad, as ways of coping with poverty. Then discuss whether poverty and citizenship categories considered essential in this study, because from them we seek to understand how families surveyed are positioned before the program, their individual and collective insights gained that experience, regarding the understanding and exercise rights. The theoretical and analytical basis for the study in the listed categories are respaldadas on authors such as: Behring e Boschetti (2008, 2011), Silva (2006, 2008, 2010, 2012), Vera Telles (2006), Yazbek (2007), Suplicy (2002), Sposati (1997), Bourdieu (1989), Da Matta (1997), Rocha, Carvalho, Braga (2010), de Queiroz (1991) and others. Regarding methodology, evaluative research is delineated from the qualitative approach, using the technique of studying the life history of the four selected families. Thus , the report is for these historical moments, analyzing "the forces and counter forces " that surround and influence, whose developments occur in all their behaviors and attitudes. As regards the conclusion is analyzed, however contradictory, evaluative meanings because the program strengthens the autonomy of these women and there is the incentive to professionalization, but still affects their families overcome poverty in which they live, with all its particularities therefore does not provide the full exercise of rights attached to "citizenship".